The association of myocardial strain with cardiac magnetic resonance and clinical outcomes in patients with acute myocarditis - Soeiro, Alexandre M.; Bossa, Aline S.; César, Maria C.; Leal, Tatiana C. A. T.; Garcia, Guilherme; Fonseca, Rafael A.; Nakamura, Débora; Guimarães, Patrícia O.; Soeiro, Maria C. F. A.; Serrano, Carlos V.; Soares, Paulo R.; Mueller, Christian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: The role of myocardial strain in risk prediction for acute myocarditis (AMC) patients, measured by cardiac magnetic resonance (CMR), deserves further investigation. Our objective was to evaluate the association between myocardial strain measured by CMR and clinical events in AMC patients. Material and methods: This was a prospective single-center study of patients with AMC. We included 100 patients with AMC with CMR confirmation. The primary outcome was the composite of all-cause mortality, heart failure and AMC recurrence in 24 months. A subgroup analysis was performed on a sample of 36 patients who underwent a second CMR between 6 and 18 months. The association between strain measures and clinical events or an increase in left ventricular ejection fraction (LVEF) was explored using Cox regression analysis. Global peak radial, circumferential and longitudinal strain in the left and right ventricles was assessed. ROC curve analysis was performed to identify cutoff points for clinical event prediction. Results: The mean follow-up was 18.7 + 2.3 months, and the composite primary outcome occurred in 26 patients. The median LVEF at CMR at baseline was 57.5% (14.6%). LV radial strain (HR = 0.918, 95% CI: 0.858-0.982, p = 0.012), LV circumferential strain (HR = 1.177, 95% CI: 1.046-1.325, p = 0.007) and LV longitudinal strain (HR = 1.173, 95% CI: 1.031-1.334, p = 0.015) were independently associated with clinical event occurrence. The areas under the ROC curve for clinical event prediction were 0.80, 0.79 and 0.80 for LV radial, circumferential, and longitudinal strain, respectively. LV longitudinal strain was independently correlated with prognosis (HR = 1.282, CI 95%: 1.022-1.524, p = 0.007), even when analyzed together with ejection fraction and delayed enhancement. LV and right ventricle (RV) strain were not associated with an increase in LVEF. Finally, when the initial CMR findings were compared with the follow-up CMR findings, improvements in the measures of LV and RV myocardial strain were observed. Conclusion: Measurement of myocardial strain by CMR can provide prognostic information on AMC patients. LV radial, circumferential and longitudinal strain were associated with long-term clinical events in these patients.